Yttrium-stabilized zirconia bead and preparation process thereof
By adding oxide, aluminum, and modified polypropylene acid to the oxide material, the problem of decline in mechanical properties in low -temperature environments in low -temperature environments is solved, and the effect of improving hardness, density and mechanical properties has been extended.
Patent Information
- Application Number
- CN202411874122.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-01-21
AI Technical Summary
When existing zirconia materials are used in the temperature zone of 100~400℃ for a long time, especially in humid environments, it will cause significant decline in its mechanical properties and microcracks, which will affect its service life.
Yttrium-stabilized zirconia beads and their preparation process are used to improve the dispersion effect and mechanical properties by adding yttrium oxide and alumina, and using modified polyacrylic acid as a dispersant. Modified polyacrylic acid is obtained through free radical polymerization and has a "comb-like" structure, which improves the heat resistance and impact resistance of the dispersant.
Significantly improves the hardness, density and mechanical properties of zirconia beads, prevents low-temperature aging, extends service life, and improves grinding efficiency.
Smart Images

Figure CN119330707A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to yttrium-stabilized zirconia beads and a preparation process thereof. Background Art
[0002] Zirconia is an inorganic non-metallic material that is resistant to high temperatures, corrosion, and wear, and has good electrical conductivity. Currently, the application of zirconia has spread across many industries.
[0003] Zirconia will undergo plastic deformation, expansion and grain growth when it reaches a certain temperature. It is one of the earliest ceramic materials studied for phase change toughening. By utilizing its phase change characteristics, ceramic products with extremely high fracture toughness and bending strength can be manufactured. In the field of modern industrial ceramics, zirconia ceramics have become the second largest system after alumina ceramics.
[0004] Zirconia beads are ceramic spheres made of zirconium oxide as the main material, known for their smooth surface and pearl-like luster. They have high toughness and impact resistance and are not easy to break even at high speeds. The wear resistance of zirconia beads is excellent, 30 to 50 times that of glass beads, and due to their high density, the grinding efficiency is also higher. The application of zirconia beads is very wide, including but not limited to electronic ceramics, magnetic materials, zirconium oxide, silicon oxide, zirconium silicate, titanium dioxide, pharmaceutical food, pigments, dyes, inks and specialty chemical industries. They are used to grind materials such as heavy calcium carbonate, kaolin, titanium dioxide. In addition, zirconia beads are also used as abrasive particles in products such as sandpaper, grinding wheels, emery cloth, and cutting wheels. In steel smelting, they are also used as refractory materials and backing materials. Due to their excellent biocompatibility and mechanical strength, zirconia beads are also used in medical devices such as medical dentures and artificial joints. In the field of electronic materials, they are used to manufacture ceramic capacitors and piezoelectric components. In addition, zirconium oxide beads are also used as catalyst carriers in fields such as liquid phase catalytic reactions and automobile exhaust purification.
[0005] CN109336590A relates to a magnesium oxide partially stabilized zirconium oxide, a magnesium oxide partially stabilized zirconium oxide ceramic, and a preparation method and application thereof. The preparation method of the magnesium oxide partially stabilized zirconium oxide comprises: mixing a zirconium source, a magnesium source and a dispersant in a solvent according to a molar ratio of zirconium element to magnesium element of 4:1 to 40:1 to obtain a mixed solution; adjusting the pH value of the mixed solution to 2 to 3, and then adding propylene oxide to the mixed solution under continuous stirring and 60°C to 80°C, until the pH value of the reaction system reaches 7 to 8, stopping the addition of propylene oxide, and then performing solid-liquid separation to obtain a precursor; mixing the precursor with water, and performing a hydrothermal reaction at 150°C to 220°C, and performing solid-liquid separation to obtain magnesium oxide partially stabilized zirconium oxide. The method can prepare magnesium oxide partially stabilized zirconium oxide with high sintering activity, so as to obtain magnesium oxide partially stabilized zirconium oxide ceramics with both high flexural strength and high toughness.
[0006] CN115093217A relates to a preparation method of gray zirconia ceramics, comprising the following steps: S1: adding a ceramic base material and a dispersant into pure water to obtain a primary slurry, grinding the primary slurry to obtain a primary slurry; S2: stirring the primary slurry and adding a colorant, and then adding an alkaline solution, adjusting the pH to 7-10, to obtain a secondary slurry; S3: sequentially adding a plasticizer and a lubricant to the obtained secondary slurry to obtain a tertiary slurry; S4: sequentially spraying granulation, pressing, debinding treatment and sintering treatment of the obtained tertiary slurry to obtain a gray zirconia ceramic; the sintering treatment is carried out in a weakly reducing atmosphere. It also relates to a gray zirconia ceramic. The gray zirconia ceramic can be formed within a temperature range suitable for sintering zirconia ceramics, has better physical properties and can present a gray tone; and the main raw material component yttrium-stabilized zirconia ceramic powder and the raw materials for making the colorant are easy to obtain and cheap, saving production.
[0007] The main obstacle of zirconia ceramic materials is the low-temperature degradation of the material. When used for a long time in the temperature range of 100~400℃ (especially in a humid environment), its mechanical properties will be significantly reduced, accompanied by microscopic or macroscopic microcracks on the surface. Therefore, it is necessary to develop a zirconia material with better wear resistance and aging resistance to increase its service life. Summary of the invention
[0008] In view of the above-mentioned defects in the prior art, the technical problem to be solved by the present invention is to provide a yttrium-stabilized zirconia bead and a preparation process thereof.
[0009] In the preparation process of zirconia beads, dispersants are usually added to improve the dispersibility of the powder and prevent the aggregation of powder particles, thereby avoiding defects in the final sintered product and improving the strength and reliability of the product. Dispersants achieve this goal in two main ways: one is to increase the repulsive force between particles and achieve electrostatic stability by changing the pH value; the other is to add polymer molecules, which, when adsorbed on the surface of the powder, prevent the particles from physical contact and thus avoid aggregation, which is called steric stabilization. In addition, dispersants can also improve dispersibility by converting the hydrophilic surface of ceramic particles into hydrophobicity to meet the needs of non-aqueous suspensions. However, current dispersants such as polyacrylic acid have the defects of poor compatibility, heat resistance and impact resistance. Therefore, the present invention provides a modified polyacrylic acid, which is obtained by free radical polymerization of modified monomers with sodium 2-methylprop-2-ene-1-sulfonate and maleic anhydride. Since the raw materials have different side chain groups, the obtained polyacrylic acid is not linear, but similar to a "comb", so the dispersion effect is better, and different side chain groups may give different properties to the modified polyacrylic acid, thereby improving heat resistance and impact resistance, and one end of the dispersant is adsorbed on solid particles, and the other end is fully extended in the solvent, generating steric repulsion between each other, forming a steric stabilization mechanism. At a certain concentration, the protective layer with strong lyophilicity and considerable thickness formed by the adsorption of the polymer on the surface of the colloidal particles can effectively shield the van der Waals force between the particles, greatly improving the stability of the dispersed system. In addition, the carboxyl group on the modified polyacrylic acid can form a hydrogen bond with the hydroxyl group on the surface of zirconium oxide, thereby enhancing the adsorption effect. In addition, the sulfonic acid group has a large polar surface area and solvent exclusion volume, which is conducive to efficient desolvation with ceramic particles through electrostatic interaction, thereby enhancing the adsorption effect.
[0010] The present invention also improves the performance of the finished zirconia beads by adding yttrium oxide and aluminum oxide. Yttrium oxide, as a stabilizer, can stabilize the tetragonal phase of zirconia and prevent it from transforming into a monoclinic phase at room temperature, while aluminum oxide can hinder the growth of tetragonal zirconia grains and play a role in particle reinforcement, effectively preventing the low-temperature aging phenomenon from expanding into the interior of the material. The two together improve the comprehensive mechanical properties of zirconia.
[0011] To achieve the above object, the present invention provides a yttrium-stabilized zirconia bead, comprising the following components in parts by weight: 40-60 parts of water, 94-95 parts of zirconium oxide, 5-6 parts of yttrium oxide, 0.05-1.5 parts of aluminum oxide, 1-2 parts of modified polyacrylic acid and 0.5-1.5 parts of a binder.
[0012] The preparation process of the modified polyacrylic acid comprises the following steps: Maleic anhydride, water and sodium hydroxide aqueous solution are heated and stirred, and then sodium 2-methylprop-2-ene-1-sulfonate is added. After continuing to heat, the modified monomer and ammonium persulfate are added, and after free radical polymerization, aging, pH adjustment and cooling are performed to obtain the product.
[0013] Furthermore, the preparation process of the modified polyacrylic acid comprises the following steps: Heat maleic anhydride, water and sodium hydroxide aqueous solution to 50-60°C, stir evenly, then add sodium 2-methylprop-2-ene-1-sulfonate, continue to heat to 80-100°C, add modified monomer and ammonium persulfate aqueous solution, stir for 1-2 hours, age for 20-40 minutes, cool to 50-60°C, adjust pH to neutral with sodium hydroxide aqueous solution; cool to room temperature to obtain the product.
[0014] Furthermore, the mass ratio of maleic anhydride to water, sodium hydroxide aqueous solution, sodium 2-methylprop-2-ene-1-sulfonate, modified monomer, and ammonium persulfate aqueous solution is 1:(5~6):(1~2):(1~3):(2~10):(0.5~1.5).
[0015] Preferably, the modified monomer is one of acrylic acid, 2-methylenepentadecanoic acid or 2-(2-naphthyl)-2-acrylic acid.
[0016] Furthermore, the binder is polyvinyl alcohol.
[0017] A preparation process of yttrium-stabilized zirconia beads comprises the following steps: S1. Add zirconium oxide, yttrium oxide and aluminum oxide in a certain proportion to a ball mill, add water and modified polyacrylic acid, and grind to a slurry particle size D 50 <0.5μm, add binder and mix evenly; S2, spray granulating the slurry; S3, rolling the prepared granulated powder to obtain a grinding medium embryo; S4, sintering the green embryo for 1-3 hours; S5. Polishing the sintered yttrium-stabilized zirconia beads to obtain finished yttrium-stabilized zirconia beads.
[0018] Furthermore, during the granulation, the rotation speed of the atomizer of the granulation tower is 9000-10000 r / min.
[0019] Furthermore, the inlet temperature during granulation is 200-250°C.
[0020] Furthermore, the outlet temperature during granulation is 100-120°C.
[0021] Furthermore, the sintering temperature is 1400-1450°C.
[0022] Beneficial effects of the present invention: 1. Compared with the prior art, the present invention provides a modified polyacrylic acid obtained by free radical polymerization of a modified monomer with sodium 2-methylprop-2-ene-1-sulfonate and maleic anhydride. Since the raw materials have different side chain groups, the obtained polyacrylic acid is not linear but "comb-shaped", so the dispersion effect is better. The dispersant affects the stability and uniformity of the zirconium oxide slurry, thereby affecting the mechanical properties of the sintered product.
[0023] 2. The present invention improves the performance of the finished zirconia beads by adding yttrium oxide and aluminum oxide. Yttrium oxide, as a stabilizer, can stabilize the tetragonal phase of zirconia and prevent it from transforming into a monoclinic phase at room temperature, while aluminum oxide can hinder the growth of tetragonal zirconia grains and play a role in particle reinforcement, effectively preventing the low-temperature aging phenomenon from expanding into the interior of the material. The two together improve the comprehensive mechanical properties of zirconia. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a cross-sectional view of the yttrium-stabilized zirconia beads of Example 1.
[0025] Figure 2 This is a surface image of the yttrium-stabilized zirconia beads of Example 1 under a stereo microscope. DETAILED DESCRIPTION
[0026] 2-Methylene-pentadecanoic acid, CAS: 104157-04-2.
[0027] 2-(2-naphthalenyl)-2-propenoic acid, CAS: 75029-76-4.
[0028] Sodium 2-methylprop-2-ene-1-sulfonate, CAS: 194810-55-4.
[0029] Polyvinyl alcohol, PVA-1799, Inner Mongolia Shuangxin Environmental Protection Materials Co., Ltd.
[0030] Sodium polyacrylate, Model: 445N, Dow Chemical.
[0031] Example 1 A preparation process of yttrium-stabilized zirconia beads comprises the following steps, measured in parts by weight: S1. Add 94 parts of zirconium oxide, 5 parts of yttrium oxide, and 1 part of aluminum oxide into a ball mill, add 50 parts of water and 1.5 parts of modified polyacrylic acid, and grind to a slurry particle size of D50 <0.5μm, add 1 part of polyvinyl alcohol and mix well; S2, spray granulation of the slurry, the granulation tower atomizer speed is 9500r / min, the inlet temperature is 230℃, and the outlet temperature is 110℃; S3, rolling the prepared granulated powder to obtain a grinding medium embryo; S4, sintering the green embryo at 1430°C for 2h; S5. Polishing the sintered yttrium-stabilized zirconia beads to obtain finished yttrium-stabilized zirconia beads.
[0032] The preparation process of the modified polyacrylic acid comprises the following steps, calculated in parts by weight: Heat 1 part of maleic anhydride with 5.5 parts of water and 1.6 parts of 1 mol / L sodium hydroxide aqueous solution to 55°C and stir evenly, then add 1.5 parts of 2-methylprop-2-ene-1-sulfonic acid sodium, continue to heat to 90°C, add 2.5 parts of acrylic acid and 1.2 parts of 5 wt% ammonium persulfate aqueous solution, stir for 2 hours, age for 30 minutes, cool to 60°C, adjust pH to 7 with 1 mol / L sodium hydroxide aqueous solution, and cool to room temperature to obtain the product. Example 1 The cross-sectional view of yttrium stabilized zirconia beads is shown in FIG. Figure 1 The surface of the yttrium stabilized zirconia beads of Example 1 under a stereo microscope is shown in FIG. Figure 2 .
[0033] Example 2 The method is substantially the same as Example 1, except that 2.5 parts of acrylic acid are replaced by 8.83 parts of 2-methylenepentadecanoic acid.
[0034] Example 3 The method is substantially the same as Example 1, except that 2.5 parts of acrylic acid are replaced by 6.88 parts of 2-(2-naphthyl)-2-acrylic acid.
[0035] Example 4 The method is basically the same as Example 1, except that the amount of modified polyacrylic acid is 1 part.
[0036] Example 5 The method is basically the same as Example 1, except that the amount of modified polyacrylic acid is 2 parts.
[0037] Comparative Example 1 A preparation process of yttrium-stabilized zirconia beads comprises the following steps, measured in parts by weight: S1. Add 94 parts of zirconium oxide, 5 parts of yttrium oxide, and 1 part of aluminum oxide into a ball mill, add 50 parts of water, and grind to a slurry particle size of D 50 <0.5μm, add 1 part of polyvinyl alcohol and mix well; S2, spray granulation of the slurry, the granulation tower atomizer speed is 9500r / min, the inlet temperature is 230℃, and the outlet temperature is 110℃; S3, rolling the prepared granulated powder to obtain a grinding medium embryo; S4, sintering the green embryo at 1430°C for 2h; S5. Polishing the sintered yttrium-stabilized zirconia beads to obtain finished yttrium-stabilized zirconia beads.
[0038] Comparative Example 2 A preparation process of yttrium-stabilized zirconia beads comprises the following steps, measured in parts by weight: S1. Add 94 parts of zirconium oxide, 5 parts of yttrium oxide, and 1 part of aluminum oxide into a ball mill, add 50 parts of water and 1.5 parts of sodium polyacrylate, and grind to a slurry particle size of D 50 <0.5μm, add 1 part of polyvinyl alcohol and mix well; S2, spray granulation of the ground slurry, the granulation tower atomizer speed is 9500r / min, the inlet temperature is 230℃, and the outlet temperature is 110℃; S3, rolling the prepared granulated powder to obtain a grinding medium embryo; S4, sintering the green embryo at 1430°C for 2h; S5. Polishing the sintered yttrium-stabilized zirconia beads to obtain finished yttrium-stabilized zirconia beads.
[0039] Test Example 1 The Vickers hardness and density of the yttrium-stabilized zirconia beads prepared in the examples and control examples were tested. The Vickers hardness test was conducted in accordance with GB / T16534-2009 Test Method for Hardness of Fine Ceramics at Room Temperature, and the density test was conducted in accordance with GB / T2413-1980 Measurement Method for Bulk Density of Piezoelectric Ceramic Materials. The specific results are shown in Table 1.
[0040] Table 1 Hardness and density test results of yttrium stabilized zirconia beads Experimental protocol Hardness / Hv Density / g / cm3 Example 1 1342.1 6.04 Example 2 1344.5 6.05 Example 3 1350.2 6.05 Example 4 1340.3 6.03 Example 5 1345.6 6.04 Comparative Example 1 1340.1 6.01 Comparative Example 2 1338.7 6.02 Vickers hardness and density of zirconia beads are two important physical performance parameters. The Vickers hardness of zirconia beads is an important indicator of their wear resistance. The density of zirconia beads is closely related to their grinding efficiency. The greater the density, the higher the grinding efficiency. This is because high-density zirconia beads generate more kinetic energy when rotating in the sand mill, thereby improving grinding efficiency. The hardness and density of zirconia beads are also related to their compressive strength and impact resistance. These performance parameters are crucial to the performance of zirconia beads in high-energy grinding processes.
[0041] The present invention achieves grain refinement by adding yttrium oxide and aluminum oxide, while increasing the amount of liquid phase, filling the gaps between the grains, and increasing the density. The increase in density means that the voids inside the material are reduced, thereby increasing the hardness of the material. The density also has an important influence on the density. Therefore, the zirconia beads prepared by the present invention have higher hardness and density.
[0042] Test Example 2 The yttrium-stabilized zirconia beads prepared in the examples and control examples were tested for flexural strength, fracture toughness and self-abrasion. The flexural strength test was carried out with reference to GB / T4741-1999 Test method for flexural strength of ceramic materials, the fracture toughness test was carried out with reference to GB / T14389-1993 Test method for impact toughness of engineering ceramics, and the self-abrasion test was carried out with reference to JC / T2136-2012 Microcrystalline zirconia grinding medium balls. The specific results are shown in Table 2.
[0043] Table 2 Mechanical properties and wear resistance test results of yttrium stabilized zirconia beads Flexural strength is a measure of the ability of zirconia beads to resist damage when subjected to bending forces. High flexural strength means that the zirconia beads can withstand large forces during the grinding process without breaking, which is crucial to ensure grinding efficiency and extend the life of the beads.
[0044] Fracture toughness refers to the ability of a material to resist crack propagation in the presence of cracks. The high fracture toughness of zirconia beads means that they are not prone to breakage when subjected to impact or stress concentration, which is very important for maintaining the integrity of the grinding media and improving grinding efficiency.
[0045] The self-wear rate refers to the speed at which the zirconia beads wear out during the grinding process. Low self-wear rates mean that the zirconia beads can maintain good shape and size after long-term use, reducing the impact of impurities caused by wear on the quality of the ground products, while also reducing the frequency of bead replacement and reducing costs.
[0046] As can be seen from Table 2, the mechanical properties and wear resistance of the zirconium oxide beads in the embodiment are significantly better than those in the control example. This may be because the dispersant affects the stability and uniformity of the zirconium oxide slurry, thereby affecting the flexural strength and fracture toughness of the finished product after sintering. Compared with the control example 2, the modified polyacrylic acid in the embodiment 1 to 3 is used as the dispersant. Compared with the conventional linear polyacrylic acid, the modified polyacrylic acid in the embodiment is similar to a "comb", so the dispersion effect is better. One end of the dispersant is adsorbed on the solid particles, and the other end is fully extended in the solvent, generating a steric repulsion between each other, forming a steric stabilization mechanism. At a certain concentration, the protective layer with a strong lyophilicity and considerable thickness formed by the adsorption of the polymer on the surface of the colloidal particles can effectively shield the van der Waals force between the particles, greatly improving the stability of the dispersed system. In addition, the carboxyl group on the modified polyacrylic acid can form a hydrogen bond with the hydroxyl group on the surface of the zirconium oxide, thereby enhancing the adsorption effect. In addition, the sulfonic acid group has a large polar surface area and solvent exclusion volume, which is conducive to efficient desolvation with the ceramic particles through electrostatic interaction, thereby enhancing the adsorption effect. Therefore, the dispersion of the slurry in the embodiment is better, and the powder is not easy to agglomerate and thus is not easy to affect the sintering effect. Compared with embodiments 1 and 2, embodiment 3 has better mechanical properties, which is because different side chain groups may give different properties to the modified polyacrylic acid, thereby improving heat resistance and impact resistance, and the side chain in embodiment 3 has a naphthalene ring, so the mechanical properties are better.
[0047] In addition, the present invention improves the performance of the finished zirconia beads by adding yttrium oxide and aluminum oxide. Yttrium oxide, as a stabilizer, can stabilize the tetragonal phase of zirconia and prevent it from transforming into a monoclinic phase at room temperature, while aluminum oxide can hinder the growth of tetragonal zirconia grains and play a role in particle reinforcement, effectively preventing the low-temperature aging phenomenon from expanding into the interior of the material. The two together improve the wear resistance and mechanical properties of zirconia.
[0048] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A yttrium-stabilized zirconia bead, characterized in that: The invention comprises the following components in parts by weight: 40-60 parts of water, 94-95 parts of zirconium oxide, 5-6 parts of yttrium oxide, 0.05-1.5 parts of aluminum oxide, 1-2 parts of modified polyacrylic acid and 0.5-1.5 parts of a binder; The preparation process of the modified polyacrylic acid comprises the following steps: Maleic anhydride, water and sodium hydroxide aqueous solution are heated and stirred, and then sodium 2-methylprop-2-ene-1-sulfonate is added. After continuing to heat, the modified monomer and ammonium persulfate are added, and after free radical polymerization, aging, pH adjustment and cooling are performed to obtain the product.
2. The yttrium-stabilized zirconia beads according to claim 1, characterized in that The preparation process of the modified polyacrylic acid comprises the following steps: Heat maleic anhydride, water and sodium hydroxide aqueous solution to 50-60°C, stir evenly, then add sodium 2-methylprop-2-ene-1-sulfonate, continue to heat to 80-100°C, add modified monomer and ammonium persulfate aqueous solution, stir for 1-2 hours, age for 20-40 minutes, cool to 50-60°C, adjust pH to neutral with sodium hydroxide aqueous solution; cool to room temperature to obtain the product.
3. The yttrium-stabilized zirconia beads according to claim 2, characterized in that The mass ratio of the maleic anhydride to water, sodium hydroxide aqueous solution, sodium 2-methylprop-2-ene-1-sulfonate, modified monomer, and ammonium persulfate aqueous solution is 1:(5-6):(1-2):(1-3):(2-10):(0.5-1.5).
4. The yttrium-stabilized zirconia beads according to claim 1, characterized in that The binder is polyvinyl alcohol.
5. The process for preparing yttrium-stabilized zirconia beads according to any one of claims 1 to 4, characterized in that: The steps include: S1. Add zirconium oxide, yttrium oxide and aluminum oxide in a certain proportion to a ball mill, add water and modified polyacrylic acid, and grind to a slurry particle size D 50 <0.5μm, add adhesive and mix evenly; S2, spray granulating the slurry; S3, rolling the prepared granulated powder to obtain a grinding medium embryo; S4, sintering the green embryo for 1-3 hours; S5. Polishing the sintered yttrium-stabilized zirconia beads to obtain finished yttrium-stabilized zirconia beads.
6. The process for preparing yttrium-stabilized zirconia beads according to claim 5, characterized in that: During the granulation, the rotation speed of the atomizer of the granulation tower is 9000-10000 r / min.
7. The process for preparing yttrium-stabilized zirconia beads according to claim 5, characterized in that: The inlet temperature during the granulation is 200-250°C.
8. The process for preparing yttrium-stabilized zirconia beads according to claim 5, characterized in that: The outlet temperature during the granulation is 100-120°C.
9. The process for preparing yttrium-stabilized zirconia beads according to claim 5, characterized in that: The sintering temperature is 1400-1450°C.
Citation Information
Patent Citations
MgO partially stabilized ZrO, MgO partially stabilized ZrO ceramic, preparation methods of MgO partially stabilized ZrO and MgO partially stabilized ZrO ceramic and application of MgO partially stabilized ZrO ceramic
CN109336590A
Branched polyacrylic acid dispersant, and preparation method and application thereof
CN102775546A
Comb type polycarboxylic acid efficient ceramic water reducer and preparation method and application thereof
CN103833941A
Preparation method of yttrium oxide-stabilized zirconia pelletized powder
CN104129989A
Yttrium-stabilized zirconia and production process thereof
CN111875375A
Cited By
PTC ceramic material and preparation method thereof
CN121248281A